A partition design for a rotary shelf system based on ABC classification. Issue 1 (January 2021) - Liu, Yong; Tang, Wei; Ma, Yunfeng; Xie, Qi
Abstract: On the basis of the traditional ABC classification method, this paper determines another standard to subdivide the goods, that is, hierarchical ABC classification method. The calculation shows that, based on the hierarchical ABC classification method, the efficiency of multi-layer horizontal rotating shelves is increased by 26.94% and vertical shelves by 37.25%. The partition design scheme is helpful to optimize the operation efficiency of the rotating shelf warehousing system and verifies the validity and rationality of the partition design.